Significados de la Violencia Psicológica a través de las Prácticas y Estilos de Crianza de una Madre Bogotana (2021)
In the present work, the meanings of psychological violence were investigated through the parenting styles and practices of a mother from Bogotá, a critical social approach was used, with a type of qualitative research; the investigation design with which we worked was the phenomenological and narrative interview as an instrument for collecting information and for the synthesis a procedure matrix and a results matrix were used within the inductive method; the sample was from a 26-year-old woman from Bogotá, mother of two children. As a conclusion, The meanings are built from his life history and his experiences with his caregivers; in these antecedents the styles and practices of parenting that he exercises with his children are reflected, within which he presents negligence, non-observance and deficiencies in providing a permanent affective bond that provides security and confidence in children for future relationships.